Snapshots of Dynamic Adaptation: Two‐Dimensional Molecular Architectonics with Linear Bis‐Hydroxamic Acid Modules. Issue 52 (27th November 2019) - Jing, Chao; Zhang, Bodong; Synkule, Sabine; Ebrahimi, Maryam; Riss, Alexander; Auwärter, Willi; Jiang, Li; Médard, Guillaume; Reichert, Joachim; Barth, Johannes V.; Papageorgiou, Anthoula C.
Abstract: Linear modules equipped with two terminal hydroxamic acid groups act as the building block of diverse two‐dimensional supramolecular motifs and patterns with room‐temperature stability on the close‐packed single‐crystal surfaces of silver and gold, revealing a complex self‐assembly scenario. By combining multiple investigation techniques (scanning tunneling microscopy, atomic force microscopy, X‐ray photoelectron spectroscopy, and density functional theory calculations), we analyze the characteristics of the ordered assemblies which range from close‐packed structures to polyporous networks featuring an exceptionally extended primitive unit cell with a side length exceeding 7 nm. The polyporous network shows potential for hosting and promoting the formation of chiral supramolecules, whereas a transition from 1D chiral randomness to an ordered racemate is discovered in a different porous phase. We correlate the observed structural changes to the adaptivity of the building block and surface‐induced changes in the chemical state of the hydroxamic acid functional group. Abstract : Let′s tessellate : The complex evolution of structure as a function of the chemical state is visualized by scanning probe microscopy and X‐ray photoelectron spectroscopy. With progressive deprotonation of an adsorbate on Ag(111), complex networks featuring chiral pores are revealed. Their functionality is exemplified in a polyporous network where chiral supramolecular guests form enantioselectively.